1999
DOI: 10.1093/ajcn/70.6.1009
|View full text |Cite
|
Sign up to set email alerts
|

High–monounsaturated fatty acid diets lower both plasma cholesterol and triacylglycerol concentrations

Abstract: Background: Low-fat diets increase plasma triacylglycerol and decrease HDL-cholesterol concentrations, thereby potentially adversely affecting cardiovascular disease (CVD) risk. High-monounsaturated fatty acid (MUFA), cholesterol-lowering diets do not raise triacylglycerol or lower HDL cholesterol, but little is known about how peanut products, a rich source of MUFAs, affect CVD risk.Objective: The present study compared the CVD risk profile of an Average American diet (AAD) with those of 4 cholesterol-lowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
317
6
15

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(362 citation statements)
references
References 27 publications
24
317
6
15
Order By: Relevance
“…Our results are in agreement with those previously published for other tree nuts (Rajaram et al, 2001;Hyson et al, 2002) and other MUFA-rich foods (Grundy, 1986;Kris-Etherton et al, 1999a). The present study also demonstrated that a high-MUFA-rich diet had the added benefit of not increasing TAG, as the lowcholesterol diets recommended by the American Heart Association tend to do (Ginsberg et al, 1990).…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Ssupporting
confidence: 93%
“…Our results are in agreement with those previously published for other tree nuts (Rajaram et al, 2001;Hyson et al, 2002) and other MUFA-rich foods (Grundy, 1986;Kris-Etherton et al, 1999a). The present study also demonstrated that a high-MUFA-rich diet had the added benefit of not increasing TAG, as the lowcholesterol diets recommended by the American Heart Association tend to do (Ginsberg et al, 1990).…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Ssupporting
confidence: 93%
“…Almonds are low in saturated fatty acids and high in unsaturated fatty acids; 91% to 94% of total lipids are comprised of oleic acid and linoleic acid 29. This fatty acid profile likely contributed to the observed LDL‐C reduction in the current study 30. Furthermore, the CHOC did not change the level of LDL‐C.…”
Section: Discussionmentioning
confidence: 60%
“…Clinical and biomedical studies have shown that cardiovascular disease (CVD) risk factors can be improved by the isoenergetic replacement of saturated fatty acids (SFA) with -E-mail: k.e.kliem@reading.ac.uk cis-monounsaturated fatty acids (MUFA) in the human diet (Kris-Etherton et al, 1999;Mensink et al, 2003). Milk and dairy products are the major source of SFA in the European diet (Hulshof et al, 1999;Henderson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%